Pecularities of Azerbaijan’s political culture after 2020 Third Artsakh War: the symbol of “Iron Fist” - Geghamyan, Varuzhan; Elbakyan, Edgar (History and Culture, 2025)
The article examines the newly constructed symbol of the "iron fist" from a semiotic point of view and discusses its place in the political culture of Azerbaijan. The Azerbaijani authorities started to construct the "iron fist" as an unofficial symbol. This symbol since the end of 2020 has acquired several discursive meanings, which are related to the Third Artsakh War and directed at internal and external audiences. These discursive meanings have a strong anti-Armenian character and serve as a tool to raise the legitimacy of the foreign and domestic policies implemented by the Azerbaijani authorities, as well as to ensure broad mobilization around them.